Clinical Course of N-Methyl-D-Aspartate Receptor Encephalitis and the Effectiveness of Cyclophosphamide Treatment - Pavone, Piero; Falsaperla, Raffaele; Ruggieri, Martino; Verrotti, Alberto; Lubrano, Riccardo; Rizzo, Renata; Salomone, Salomone; Praticò, Andrea D. (Journal of Pediatric Neurology, 2017)
We describe the cases of two unrelated girls, aged 5 and 7, respectively, affected by N-methyl-D-aspartate receptor (NMDAr) encephalitis. The clinical records of both patients were reviewed retrospectively including family and personal history, clinical findings, laboratory, and neuroradiological examinations, electroencephalogram, and treatment performed during admissions to the unit. In both patients, the clinical course was slow and progressive. Both showed anti-NMDAr antibodies in serum and cerebrospinal fluid. Treatment with intravenous immunoglobulin and methylprednisolone was not efficacious in the long term, with several relapses occurring in both patients. Second-line treatment with cyclophosphamide (1 g/m2 once a month) resulted in improvement of symptoms and disappearance of clinical signs that were sustained at 24 months follow-up. Side effects included neutropenia in one patient.
Keywords: NMDAr; encephalitis; intravenous immunoglobulins; steroids; cyclophosphamide